(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This article explores the pervasive influence of food marketing on nutrition research, policy, and consumer behavior, examining its impact on public health efforts to combat obesity and diet-related diseases. The paper synthesizes key findings across three critical domains: corporate influence on nutrition research, marketing’s impact on consumer behavior, and the role of the food lobby in shaping public policy. It reveals how industry-sponsored research tends to favor processed foods, creating biases that influence scientific narratives. The marketing strategies employed by the food industry, including health claims, athlete endorsements, and cartoon characters, drive overconsumption of nutritionally poor products. Additionally, the article delves into the food lobby’s efforts to thwart policy reforms and block public health measures. The paper concludes by advocating for robust policies to enhance transparency in research funding, restrict misleading marketing practices, and support evidence-based measures that promote healthier dietary patterns. The overarching goal is to address the complex interplay between the food industry, nutrition research, and public policy, fostering a more health-conscious environment.